Dietary Digestible Protein Requirement in Finishing Pigs: A Study for Experimental Determination and Verification - Shengkai Li; Hui Ma; Jianliang Wu; Jihe Lu; Shiyan Qiao; Xiangfang Zeng; Junyan Zhou (Agriculture)
Crude protein, as a traditional standard for characterizing dietary nitrogen content, fails to reflect protein bioavailability. Digestible protein (DP) emphasizes the importance of total available proteins and offers better adaptability in low-protein diversified diets. The objective of this study was to establish and validate the digestible protein (DP) requirement for 80–110 kg finishing pigs (Duroc × Yorkshire × Landrace). In Experiment 1, 450 pigs were fed diets with graded DP levels (8.82–11.26%). Linear and quadratic regression models identified 9.55% DP as the optimal level, optimizing average daily gain and feed efficiency (R2 ≥ 0.94). Experiment 2 validated this requirement using three diet treatments and 270 pigs: high-protein traditional, low-protein traditional, and low-protein diversified. No significant differences were observed in growth performance, carcass traits, or meat quality among diets, confirming the robustness of 9.55% DP across formulations. Plasma urea nitrogen and total amino acids increased linearly with DP (p < 0.05), while hepatic transcriptomics revealed immune and metabolic partial impairments in high-protein traditional diet pigs, which may be linked to nitrogen overload. Muscle tissues from different treatment groups showed minimal transcriptional differences, emphasizing efficient protein utilization when amino acid requirements are met. This study demonstrates that 9.55% DP, combined with balanced amino acids, supports productivity in both traditional and diversified diets, reducing reliance on resource-intensive feed ingredients. These findings advocate for DP as a precise metric in swine production, thereby promoting sustainable development.